2023
DOI: 10.3390/children10061074
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing and Its Association with Nocturnal Enuresis at the Primary Schools in Saudi Arabia: A Cross-Sectional Study

Ali Abdullah Alshehri,
Mohamed Soliman Hassan Zaki,
Sameh Osama Nour
et al.

Abstract: The correlation between nocturnal enuresis (NE) and sleep-disordered breathing (SDB) was reported. We aim to determine whether there is an association between NE and SDB in children and to assess the prevalence of SDB and NE in primary school children aged 6–12 years in Saudi Arabia. A cross-sectional observational study was conducted among the caregivers of children aged 6–12 years in all Saudi Arabia regions. The data were gathered through a self-administered online questionnaire. It included demographic inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Meanwhile, in Jazan province, Sherah et al reported a substantially greater prevalence of enuresis by 52.6%, in the younger age group from 5-12 years [ 9 ]. An overall estimate of enuresis in Saudi Arabia was 76.4% in the age group from 6 to 12 years [ 10 ]. A lower prevalence in our study compared to the other local studies can be attributed to the smaller sample size and the different age range.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in Jazan province, Sherah et al reported a substantially greater prevalence of enuresis by 52.6%, in the younger age group from 5-12 years [ 9 ]. An overall estimate of enuresis in Saudi Arabia was 76.4% in the age group from 6 to 12 years [ 10 ]. A lower prevalence in our study compared to the other local studies can be attributed to the smaller sample size and the different age range.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear what precise mechanism connects sleep-disordered breathing to the higher likelihood of NE. Potential independent risk factors for NE in school-age children include male gender, obesity, early bedtime, loud snoring, breathing difficulties, and mouth breathing at night (22).There are several contributing factors to the nocturnal enuresis, such as poor self-esteem, family stress, social isolation, family history, being male, increase family size, recurrent UTI, developmental delay who had down syndrome, socio-economic status, maternal educational status, age of mothers during birth, children exposed for stressful events were significant predictors of nocturnal enuresis which was found in different studies (21,(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%